Cul o 2 specific IgG3/5 antibodies predicted Culicoides hypersensitivity in a group imported Icelandic horses - Fahad Raza; Renata Ivanek; Heather Freer; Dania Reiche; Horst Rose; Sigurbjörg Torsteinsdóttir; Vilhjálmur Svansson; Sigríður Björnsdóttir; Bettina Wagner (BMC Veterinary Research, 2020)
Abstract Background Culicoides hypersensitivity (CH) is induced in horses by salivary allergens of Culicoides midges. In Iceland, the causal Culicoides species for CH are not present. Previous epidemiological data indicated that Icelandic horses are more susceptible to CH when they are exported from Iceland and first exposed to Culicoides at adult age. Horses born in countries where Culicoides is endemic, develop the disease less frequently. Here, we established a longitudinal allergy model to identify predictive and diagnostic serological biomarkers of CH. Results Sixteen adult Icelandic horses from Iceland were imported to the Northeastern United States (US) during the winter and were kept in the same environment with natural Culicoides exposure for the next two years. None of the horses showed clinical allergy during the first summer of Culicoides exposure. In the second summer, 9/16 horses (56%) developed CH. Allergen specific IgE and IgG isotype responses in serum samples were analysed using nine potential Culicoides allergens in a fluorescent bead-based multiplex assay. During the first summer of Culicoides exposure, while all horses were still clinically healthy, Cul o 2 specific IgG3/5 antibodies were higher in horses that developed the allergic disease in the second summer compared to those that did not become allergic (p = 0.043). The difference in Cul o 2 specific IgG3/5 antibodies between the two groups continued to be detectable through fall (p = 0.035) and winter of the first year. During the second summer, clinical signs first appeared and Cul o 3 specific IgG3/5 isotypes were elevated in allergic horses (p = 0.041). Cul o 2 specific IgG5 (p = 0.035), and Cul o 3 specific IgG3/5 (p = 0.043) were increased in late fall of year two when clinical signs started to improve again. Conclusions Our results identified IgG5 and IgG3/5 antibodies against Cul o 2 and Cul o 3, respectively, as markers for CH during and shortly after the allergy season in the Northeastern US. In addition, Cul o 2 specific ...